The Role of Musyawarah Values in Community Counseling in Yogyakarta - Basyid, Abd.; Sari, Cahya Pridaya; Imtiaz, Fatma; Hunainah, Fauziah (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
This study aims to explore the role of musyawarah values in community counseling in Yogyakarta. Musyawarah, as a communication practice rooted in local wisdom, functions as an effective problem-solving mechanism within community contexts, particularly when applied in counseling services. This approach helps to resolve social conflicts arising from developmental disparities in the Yogyakarta region and enhances community participation in decision-making processes. The study employs a literature review method with qualitative analysis to identify the role of musyawarah in strengthening social cohesion, preventing conflict escalation, and creating more inclusive and fair decisions. The findings indicate that musyawarah plays a crucial role in optimizing community potential and enabling them to face social changes more harmoniously.